AJARAN KARMAPHALA MENURUT SUSASTRA HINDU PERSPEKTIF DALAM KEHIDUPAN SEHARI HARI - I Nyoman Subrata (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2019)
The essence of Karmaphala teaches that there are three types of karma that are: karma that gives direct consequence, karma that has an indirect effect in which the reward is only enjoyed after death and the karma that will enjoy as a result of previous acts of life. The Hindus seyoganya understand this universal karmaphala law. Understanding that, every Hindu believer will always think long to do something, since the consequence is in line with the nature of the act to be done. Because knowing the consequences of bad actions will bring bad consequences for himself, then people will abuse themselves from bad actions. That’s why they always do good deeds, because by doing good, the consequences will be fine Whatever is done by human beings brings consequences, consequently there is good and bad quality, good results give pleasure and bad consequences to bring trouble. By doing so one must do good because everyone wants pleasure and live peacefully. The fruit of the act (karma) is called reward. The fruits of the act are not always directly perceived or enjoyed. Every act of leaving the former. There is a real container and there is an unidentified former (in the imagination and abstract) used carmavasana